A large hematometra after cervical carcinoma in situ - a case report and review of literature - Zeba Khanam; Roli Purwar; Ankita Kumari (Barpeta Obstetrics and Gynaecological Society, 2023)
The association of a pre-invasive cervical lesion with hematometra is uncommon except in cases where the former is associated with a uterine malignancy. To date, an isolated cervical preinvasive lesion (without a concomitant endometrial involvement) leading to hematometra has not been reported. We report here such a unique case and provide useful insights and highlight learning points in its management along with a brief review of literature. A postmenopausal female presented with a huge abdominopelvic mass which was later reported as a hematometra. The underlying carcinoma-in-situ of the cervix had lead to cervical stenosis. Accompanying endometritis culminated in the collection of a massive amount of blood inside the endometrial cavity.